2018
DOI: 10.1186/s12914-018-0154-6
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards help-seeking for sexual and gender-based violence in humanitarian settings: the case of Rwamwanja refugee settlement scheme in Uganda

Abstract: BackgroundSexual and gender-based violence (SGBV) remains a silent epidemic in many humanitarian settings with many survivors concealing their experiences. Attitudes towards help-seeking for SGBV is an important determinant of SGBV service use. This paper examined the association between attitudes towards seeking care and knowledge and perceptions about SGBV among men and women in a humanitarian setting in Uganda.MethodsA cross-sectional survey was conducted from May to June 2015 among 601 heads of refugee hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
(45 reference statements)
2
10
0
Order By: Relevance
“…Our finding of knowledge and awareness about health needs and available health services were consistent with the study conducted by Odwe, Undie [30] in which the authors concluded that promoting awareness and progressive attitudes towards available health care services and support or sexual and gender-based violence may encourage positive helpseeking attitudes and behaviors among Rwamwanja refugee women in Uganda.…”
Section: Discussionsupporting
confidence: 90%
“…Our finding of knowledge and awareness about health needs and available health services were consistent with the study conducted by Odwe, Undie [30] in which the authors concluded that promoting awareness and progressive attitudes towards available health care services and support or sexual and gender-based violence may encourage positive helpseeking attitudes and behaviors among Rwamwanja refugee women in Uganda.…”
Section: Discussionsupporting
confidence: 90%
“…Social justification of sexual violence as a normal act that is related to men's higher sexual needs often prevents women from seeking help or makes them underestimate the seriousness of the situation. This finding has been replicated in recent studies in other countries with traditional patriarchal views (Adinkrah, 2017;Lynch et al, 2017;Odwe et al, 2018).…”
Section: Discussionsupporting
confidence: 65%
“…In fact, women in Ghana are socialized to respond to their husbands' sexual needs. Women's perceptions of communities' tolerance of sexual violence have been shown to be an influential factor in the help-seeking behavior of refugee women in Uganda (Odwe et al, 2018).…”
Section: " I Had To Do That [What They Saw On Porn Clip] … I Didn't Hmentioning
confidence: 99%
“…Edströ m and Dolan (2019) evaluated breaking the silence against sexual harassment and activism among refugees in 2015, a group of male refugee survivors of sexual violence (SV) were able to form, rebuild and convert to activism and replicated how the struggle should be engaged and understood in line with their recovery through mutual support and lobbied communal acts, and the role of service providers and humanitarian organizations in support and suggested change in policy, support in recovery, networking, say no to male victimization in conflict areas and activism. Odwe et al (2018) investigated attitude toward seeking for support, acquaintance and sensitivities concerning SGBV among women and men in a humanitarian setting in Uganda.…”
Section: The Legal Framework-national Policies and Plansmentioning
confidence: 99%